Comparison Between Low-Dose and Standard-Dose Computed Tomography for Diagnosis of Urolithiasis - K.J.S.S. Raghu Teja; Bhamidipaty Kanaka Durgaprasad; Payala Vijayalakshmi (Asian Journal of Medical Radiological Research, 2021)
Background: Urolithiasis is the condition where there are calculi in the urinary system and the current study was implemented to evaluate the diagnostic performance of low-dose Computed Tomography (CT) with standard-dose CT for detection of urolithiasis. Subjects & Methods: Eight hundred thirty-seven individuals Individuals with clinically/sonographically suspected urolithiasis and referred for Computed Tomography (CT) evaluation at the Radiodiagnosis department were screened for the study. The study was conducted in two stages. During the first stage, individuals underwent an NCCT scan (Philips 16 slice CT scanner) with the standard-dose protocol as per the current management strategy. Individuals with CT evidence of urolithiasis were included in the second stage of the study where they were given with low dose CT. After excluding many subjects, 148 patients underwent standard-dose CT for the evaluation of urolithiasis. Additionally, 23 patients were referred directly for CT due to high clinical suspicion of urolithiasis, constituting 171 patients who underwent NCCT KUB. Among patients who underwent CT scan 16 patients were excluded from the study as no calculus was detected on NCCT. Results: Urolithiasis was seen in 155 patients who met the inclusion criteria. Among these, 26 patients declined for low-dose CT, nine patients had BMI > 35 kg/m2 and 16 patients were of age <18 years and hence were excluded from the study. Finally, 104 patients underwent low-dose CT and were included in the final analysis. The use of low tube potential setting by tube voltage reduction of 15% significantly reduced radiation dose by approximately 31% in patients undergoing CT for evaluation of urolithiasis, irrespective of their BMI. Conclusion: A combination of reduced tube potential and AEC helps to achieve optimum results for the diagnosis of urolithiasis. The study strongly supports the use of low-dose CT for diagnosis and follow-up of urolithiasis in patients who are not morbidly obese.